Study of Genotoxic Properties of Thiosonide - A. Yu. Sаvchenko; M. S. Burenkov; P. S. Bаydin; G. V. Rаmenskаya; N. V. Perovа; V. G. Kukes (Туберкулез и болезни лёгких)
The objective of the study: evaluation of mutagenic properties of thiosonide in tests of chromosomal aberrations in mammalian bone marrow cells and mutation accounting on Salmonella typhimurium strains.Subjects and methods. Studies were carried out using F1 hybrids of CBA×C57BL/6 mice, they received thiozonide in the equivalent of a therapeutic dose and 160 times above it, once and in the course of 5 injections. The genetic toxicity of thiosonide was evaluated on Salmonella typhimurium strains in the tested doses of 1,000, 100, 10, 1 and 0.1 μg per plate.Results. No mutagenic activity of thiosonide in the chromosomal aberration counting test in bone marrow cells of mice was demonstrated. The level of chromosome aberrations in the experiment did not exceed the corresponding control values. Thus, thiosonide at the therapeutic dose (25 mg/kg) and 160-fold increase above it (4,000 mg/kg) did not induce chromosomal aberrations in the bone marrow cells of mice either with single dosing or several intragastric administrations.According to the Ames test results, the number of revertant colonies in the solvent control in the CM- and CM+ variants was within the range of spontaneous fluctuations for these strains; thiosonide in all tested doses did not show mutagenic effect on the TA 100, TA 98, and TA 97 strains both with the system metabolic activation and without it.